2003
DOI: 10.1046/j.1365-4362.2003.01928.x
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of demodicidosis in eyelid basal cell carcinomas

Abstract: Demodicidosis may be one of the triggering factors of carcinogenesis in eyelid BCCs in otherwise predisposed people due to its traumatic/irritating effect or chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 22 publications
0
39
0
6
Order By: Relevance
“…Some studies have suggested a direct, significant correlation between the likelihood of mite infestation and age (29,30). All our patient groups were comparable with the controls in terms of age.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested a direct, significant correlation between the likelihood of mite infestation and age (29,30). All our patient groups were comparable with the controls in terms of age.…”
Section: Discussionmentioning
confidence: 99%
“…They have been reported to be involved in pityriasis folliculorum (Ayres, 1930), rosacea (Ayres and Ayres, 1961;Bonnar et al, 1993;Forton and Seys, 1993), pustular folliculitis (Dong and Duncan, 2006), papulopustular scalp eruptions (Purcell et al, 1986), perioral dermatitis (Hsu et al, 2009), and blepharitis (Post and Juhlin, 1963;Divani et al, 2009;Zhao et al, 2012). It is also suspected that Demodex infestation may be one of the triggering factors of carcinogenesis in eyelid basal cell carcinomas (Erbagci et al, 2003) and sebaceous adenoma (Dhingra et al, 2009). Moreover, the infestation rate in the immunocompromised population with leucocythemia (Damian and Rogers, 2003) or acquired immune deficiency syndrome (AIDS) (Clyti et al, 2005) is remarkably high and pustular eruption or seborrheic dermatitis becomes even more conspicuous.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms can disappear under acaricidal therapy, and the skin conditions can heal. Moreover, it is also suspected that Demodex infestation may be one of the triggering factors of carcinogenesis in eyelid basal cell carcinomas (Erbagci et al, 2003) and sebaceous adenoma (Dhingra et al, 2009). The infestation of Demodex has therefore been recognized by many researchers as one of the important causes of skin diseases and has increasingly become a public health concern.…”
Section: Introductionmentioning
confidence: 99%